Substitution of medical cannabis for pharmaceutical agents for pain, anxiety, and sleep. (May 2017) - Piper, Brian J; DeKeuster, Rebecca M; Beals, Monica L; Cobb, Catherine M; Burchman, Corey A; Perkinson, Leah; Lynn, Shayne T; Nichols, Stephanie D; Abess, Alexander T
A prior epidemiological study identified a reduction in opioid overdose deaths in US states that legalized medical cannabis (MC). One theory to explain this phenomenon is a potential substitution effect of MC for opioids. This study evaluated whether this substitution effect of MC for opioids also applies to other psychoactive medications. New England dispensary members ( n = 1, 513) completed an online survey about their medical history and MC experiences. Among respondents that regularly used opioids, over three-quarters (76.7%) indicated that they reduced their use since they started MC. This was significantly ( p < 0.0001) greater than the patients that reduced their use of antidepressants (37.6%) or alcohol (42.0%). Approximately two-thirds of patients decreased their use of anti-anxiety (71.8%), migraine (66.7%), and sleep (65.2%) medications following MC which significantly ( p < 0.0001) exceeded the reduction in antidepressants or alcohol use. The patient's spouse, family, and other friends were more likely to know about their MC use than was their primary care provider. In conclusion, a majority of patients reported using less opioids as well as fewer medications to treat anxiety, migraines, and sleep after initiating MC. A smaller portion used less antidepressants or alcohol. Additional research is needed to corroborate these self-reported, retrospective, cross-sectional findings using other data sources.